Democracy, property rights, income equality, and corruption - Bin Dong; Benno Torgler (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper presents theoretical and empirical evidence on the nexus between corruption and democracy. We establish a political economy model where the effect of democracy on corruption is conditional on income distribution and property rights protection. Our empirical analysis with cross-national panel data provides evidence that is consistent with the theoretical prediction. Moreover, the effect of democratization on corruption depends on the protection of property rights and income equality which shows that corruption is a nonlinear function of these variables. The results indicate that democracy will work better as a control of corruption if the property rights system works and there is a low level of income inequality. On the other hand if property rights are not secured and there is strong income inequality, democracy may even lead to an increase of corruption. In addition, property rights protection and the mitigation of income inequality contribute in a strong manner to the reduction of corruption.
Keywords: D73; H11; P16; 330; Corruption; Democracy; Income inequality; Property rights